Total ankle replacement in patients with von Willebrand disease: mid‐term results of 18 procedures. (16th February 2015) - Barg, K.; Wiewiorski, M.; Anderson, A. E.; Schneider, S. W.; Wimmer, M. D.; Wirtz, D. C.; Valderrabano, V.; Barg, A.; Pagenstert, G.
Summary von Willebrand disease (VWD) is a recognized cause of secondary ankle osteoarthritis (OA). Few studies have examined orthopaedic complications and outcomes in VWD patients treated for end‐stage ankle OA with total ankle replacement (TAR). To determine the clinical presentation, intraoperative and postoperative complications and evaluate the mid‐term outcome in VWD patients treated with TAR. Eighteen patients with VWD with mean age 47.3 years (range = 34.0–68.7) were treated for end‐stage ankle OA with TAR. The mean duration of follow‐up was 7.5 years (range = 2.9–13.2). Intraoperative and perioperative complications were recorded. Component stability was assessed with weight‐bearing radiographs. Clinical evaluation included range of motion (ROM) tests using a goniometer and under fluoroscopy using a lateral view. Clinical outcomes were analysed by a visual analogue scale, the American Orthopaedic Foot and Ankle Society hindfoot score and Short Form (36) Health Survey (SF‐36) health survey. One patient sustained an intraoperative medial malleolar fracture. In two patients delayed wound healing was observed. Two secondary major surgeries were performed. Pain level decreased from 8.2 ± 0.9 (range = 7–10) preoperatively to 1.1 ± 1.2 (range = 0–4) postoperatively. Significant functional improvement including ROM was observed. All categories of SF‐36 score showed significant improvement in quality of life. Mid‐term results of TAR in patients with VWD are encouraging. The total rate of intraoperative and postoperative complications was 33.3%. However, longer term outcomes are necessary to fully understand the clinical benefit of TAR in patients with VWD.